2011
DOI: 10.2310/7750.2011.10081
|View full text |Cite
|
Sign up to set email alerts
|

Hairless Descendants of Mexican Hairless Dogs: An Experimental Model for Studying Hypertrophic Scars

Abstract: Experimental hypertrophic scars produced in hairless dogs have morphologic properties similar to those of human hypertrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The most commonly used animal models of scarring include nude mouse models and rabbit ear models. 10 13 However, rejection response is always an avoidable problem in the establishment of nude mouse models, which involves the transplantation of human scar tissues. The rabbit ear model of scarring has much in common with human scars, such as the repair of wound surface and the histopathological structure.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used animal models of scarring include nude mouse models and rabbit ear models. 10 13 However, rejection response is always an avoidable problem in the establishment of nude mouse models, which involves the transplantation of human scar tissues. The rabbit ear model of scarring has much in common with human scars, such as the repair of wound surface and the histopathological structure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides mice, rats, rabbits and pigs, it is also possible to induce hypertrophic scars in guinea pigs and dogs [37,45]. Aksoy et al described hypertrophic scarring in guinea pigs after incision, panniculectomy and coal tar treatment, which lead to the formation of scars with histologic and clinical features of hypertrophic scars like erythema and elevation over the surrounding skin in 50% of the animals; while this method is also accompanied by mortality of 20% due to the toxic effects of coal tar [45].…”
Section: Miscellaneous Modelsmentioning
confidence: 99%
“…Aksoy et al described hypertrophic scarring in guinea pigs after incision, panniculectomy and coal tar treatment, which lead to the formation of scars with histologic and clinical features of hypertrophic scars like erythema and elevation over the surrounding skin in 50% of the animals; while this method is also accompanied by mortality of 20% due to the toxic effects of coal tar [45]. Kimura et al showed that full thickness wounds in hairless dogs form hyperpigmented scars rising above unwounded surrounding skin [37]. Compared to haired dogs, these animals form thicker scars with more blood vessels, fibroblasts and inflammatory cells, higher collagen organization and collagen nodules, which is a typical histological feature of hypertrophic scars [37].…”
Section: Miscellaneous Modelsmentioning
confidence: 99%
“…The female Red Duroc pig develops raised, thick scars following deep dermal injury, as compared with normal healing of the same wounds in the Yorkshire pig (same species control) . The Mexican Hairless dog also exhibits similar fibroproliferative scarring after injury; these lesions are not seen in other breeds of dogs . Knowledge of such interspecies and intraspecies differences can help the human wound healing researcher choose the best animal model for the question at hand, and also helps in the interpretation of results and extrapolation of data into other species and other clinical situations.…”
Section: Understanding Comparative Wound Healing To Improve Clinical mentioning
confidence: 99%